Effect of quick lime on physicochemical properties of clay soil - Bessaim Mohammed Mustapha; Bessaim Aicha; Missoum Hanifi; Bendani Karim (MATEC Web of Conferences, 2018)
Clay soils are known for their water sensitivity, which causes irreparable damage to any structure built on this type of soil. In order to avoid such problem, it is necessary to use various improvement and stabilization methods such as treatment with lime. This process has been used successfully in the field for decades. The addition of lime generates various physicochemical reactions within the soil such as cation exchange and pozzolanic reactions which are largely responsible for the improvement of the soil in question. This paper presents a study concerning the variation of physicochemical properties of clayey soil with the addition of quicklime at different percentages. Experiments were performed on two clayey soils (CL type) in order to investigate the influence of quicklime on Atterberg limits and pH. These tests were carried out in an attempt to study and follow the development and progression of various reactions occurred within the soil with various lime percentages. The results show that the addition of quicklime causes a significant improvement in soil properties by reducing plasticity and thereby improves the soil workability. It can also be found that the addition of lime increase pH of soil, which allow activating pozzolanic reactions who tend to stabilize the soil in question by formation of cementitious compounds. Finally, the pH can be considered as a relevant parameter who allows a better understanding of the reactions that occur in the soil matrix.